2014
DOI: 10.1179/1743284713y.0000000327
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of damage behaviour based on EBSD method under creep–fatigue conditions for polycrystalline nickel base superalloys

Abstract: In order to detect creep–fatigue damage before the crack initiation stage, an investigation into damage behaviour based on the electron backscattered diffraction (EBSD) method for a polycrystalline nickel base superalloy has been carried out. The average misorientation within grains increases linearly up to the initiation of cracks with the increase in creep strains. Even if stress distributions exist by stress concentration, assessment in all the damage areas allowed the evaluation of creep damage regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In order to quantify the degree of the damage induced in the material, misorientations calculated from mapping data have been quantified by various parameters such as the local misorientation, which is an averaged misorientation between neighboring measurement points (Kamaya, 2008, Calcagnotto, et al, 2010, and intra-grain misorientations, which is an averaged misorientation between the reference orientation assigned to each crystal grain and measurement points inside the grain (Mino, et al, 2003, Field, et al, 2005, Brewer et al, 2006, Kamaya, et al, 2005, Kamaya, et al, 2006. It has been shown that these parameters correlate well with the degree of plastic strain (Sutliff, 1999, Lehockey et al, 2000, Angeliu, et al, 2000, Othon and Morra, 2005, Demir, et al, 2009, Kamaya, 2009a, fatigue damage (Blochwitz, et al, 1996, Kamaya, 2009b, Kamaya, 2011b, Kamaya and Kuroda, 2011 and creep damage (Mino, et al, 2003, Boehlert, et al, 2008, Yoda, et al, 2010, Kobayashi, et al, 2011, Kobayashi, et al, 2012, Kobayashi, et al, 2013, Fujiyama, et al, 2013, Kobayashi, et al, 2014. Therefore, the magnitude of the material damage can be estimated using the correlation curve which represents the relationship between the misorientation parameters and the degree of the damage (hereafter called correlation curve).…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify the degree of the damage induced in the material, misorientations calculated from mapping data have been quantified by various parameters such as the local misorientation, which is an averaged misorientation between neighboring measurement points (Kamaya, 2008, Calcagnotto, et al, 2010, and intra-grain misorientations, which is an averaged misorientation between the reference orientation assigned to each crystal grain and measurement points inside the grain (Mino, et al, 2003, Field, et al, 2005, Brewer et al, 2006, Kamaya, et al, 2005, Kamaya, et al, 2006. It has been shown that these parameters correlate well with the degree of plastic strain (Sutliff, 1999, Lehockey et al, 2000, Angeliu, et al, 2000, Othon and Morra, 2005, Demir, et al, 2009, Kamaya, 2009a, fatigue damage (Blochwitz, et al, 1996, Kamaya, 2009b, Kamaya, 2011b, Kamaya and Kuroda, 2011 and creep damage (Mino, et al, 2003, Boehlert, et al, 2008, Yoda, et al, 2010, Kobayashi, et al, 2011, Kobayashi, et al, 2012, Kobayashi, et al, 2013, Fujiyama, et al, 2013, Kobayashi, et al, 2014. Therefore, the magnitude of the material damage can be estimated using the correlation curve which represents the relationship between the misorientation parameters and the degree of the damage (hereafter called correlation curve).…”
Section: Introductionmentioning
confidence: 99%
“…This thematic issue of MST presents a selection of peer reviewed articles [1][2][3][4][5][6][7][8][9][10][11] from the conference, focusing on recent advances in creep, fatigue, damage and fracture analysis of high temperature material and welds. The 11 papers presented report both original research and industrial experience.…”
mentioning
confidence: 99%
“…The 11 papers presented report both original research and industrial experience. The wide range of topics covered includes: finite element failure and crack growth modelling of parent materials and welds using creep continuum damage models; 1,5 effect of creep deformation on Z-phase formation, 2 creep deformation, rupture and ductility of weld metals; 3 damage behaviour characterisation under creep–fatigue for nickel based superalloys; 4 creep cavitation in stainless steels; 6 creep micro- and macro-damage in notched bars; 7 micro-mechanical creep analysis of multi-pass welds; 8 determination of heat affected zone creep properties using small punch creep testing; 10 and thermal–mechanical fatigue analysis for power plant steels using visco-plasticity models. 9,11 The majority of these topics are relevant to power plant materials (P91, P92, stainless steels and nickel based superalloys) and the structural integrity of components with an emphasis on welds.…”
mentioning
confidence: 99%